Klebsiella quasipneumoniae provides a window into carbapenemase gene transfer, plasmid rearrangements, and patient interactions with the hospital environment - Mathers, AJ; Crook, D; Vaughan, A; Barry, KE; Vegesana, K; Stoesser, N; Parikh, HI; Sebra, R; Kotay, S; Walker, AS; Sheppard, AE (American Society for Microbiology, 2019)
Several emerging pathogens have arisen as a result of selection pressures exerted by modern health care. Klebsiella quasipneumoniae was recently defined as a new species, yet its prevalence, niche, and propensity to acquire antimicrobial resistance genes are not fully described. We have been tracking inter- and intraspecies transmission of the Klebsiella pneumoniae carbapenemase (KPC) gene, blaKPC, between bacteria isolated from a single institution. We applied a combination of Illumina and PacBio whole-genome sequencing to identify and compare K. quasipneumoniae from patients and the hospital environment over 10- and 5-year periods, respectively. There were 32 blaKPC-positive K. quasipneumoniae isolates, all of which were identified as K. pneumoniae in the clinical microbiology laboratory, from 8 patients and 11 sink drains, with evidence for seven separate blaKPC plasmid acquisitions. Analysis of a single subclade of K. quasipneumoniae subsp. quasipneumoniae (n = 23 isolates) from three patients and six rooms demonstrated seeding of a sink by a patient, subsequent persistence of the strain in the hospital environment, and then possible transmission to another patient. Longitudinal analysis of this strain demonstrated the acquisition of two unique blaKPC plasmids and then subsequent within-strain genetic rearrangement through transposition and homologous recombination. Our analysis highlights the apparent molecular propensity of K. quasipneumoniae to persist in the environment as well as acquire carbapenemase plasmids from other species and enabled an assessment of the genetic rearrangements which may facilitate horizontal transmission of carbapenemases.